PENGEMBANGAN BAHAN AJAR BOOKLET DENGAN QR CODE PADA MATERI JURNAL PENYESUAIAN PERUSAHAAN DAGANG - Siti Nur Afni Oktavia; Retna Ngesti Sedyati; Tiara Tiara (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2023)
This research aims to develop teaching materials in the form of booklet with QR Code an attractive, effective and efficient on trade company adjustment journal material for class XII IPS at SMAN Ambulu. The development model used Four-D, but only until the development stage.). Data collection instruments include questionnaires, feasibility sheets, interviews, observations and documents. Data analysis includes attractiveness, effectiveness and efficiency test of teaching materials. The results showed the student attractiveness was 93.80% (very interesting). The effectiveness of teaching materials is shown by the results of t-count > t-table is 6.986 > 2.000. The efficiency of teaching materials is shown by the use a shorter time allocation than the time specified in the syllabus, from 8JP to 6JP. Booklet teaching materials with QR Code are interesting, effective and efficient. This teaching material can be used by teachers and student class XII IPS as additional teaching material and developed for other materials.